The Effect of Organizational Culture and Work Motivation on Madrasah Aliyah Teacher's Work Discipline - Telaumbanua, Azman; Zein, Achyar; Hanum, Azizah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
It is the goal of this research to determine the influence of organizational culture on the work ethics of Madrasah Aliyah teachers in Gunung Sitoli City., the impact of work motivation on the work discipline of Madrasah Aliyah teachers in Gunung Sitoli City, and the impact of organizational culture and work motivation on the work discipline of Madrasah Aliyah teachers in Gunung Sitoli City. The registrant-respondent statistics of 60 teachers are used in this study. A questionnaire was used to collect information. Simple and multiple regression techniques, as well as partial correlation, were used to analyze the data. According to the research findings, organizational culture has a positive and significant influence on teacher work discipline. There is a 28.7% effective influence on the work discipline of Madrasah Aliyah's teachers in Gunung Sitoli City if the organizational culture is higher and more positive. As a result, 28.7% of the variation in the organizational culture variable is correlated with an improvement in teacher work discipline; this is a positive and significant relationship. In other words, the more positive and motivating a teacher's work motivation is, the more effective the teacher's work discipline is. Work motivation can be predicted with a 32 percent accuracy in terms of improving teacher work discipline, and there is a joint positive and significant influence between organizational culture and work motivation.